Thrombotic complications in oncogynecological pathologies - Khakimov Galib Abdullayevich; Atakhanova Nigora Ergashevna; Tursunova Nodira Isroilovna; Sanokulova Donokhon Otabek kizi (Genius Publishing Group, 2025)
Venous thromboembolism (VTE) including deep vein thrombosis (DVT) and pulmonary embolism (PE) are well-recognized complications of gynecological malignancy and represent a leading cause of morbidity and mortality in these patients. It is known that pulmonary embolism (PE) is the cause of death in up to 15% of patients hospitalized due to a tumor. A significant proportion of cancer patients with fatal PE have a tumor of limited size or a metastatic process of minimal prevalence, i.e., we are talking about patients with a high chance of recovery or a long life. According to various researchers, from 4 to 20% of all cancer patients experience clinical manifestations of venous thromboembolism (venous thrombosis and/or pulmonary embolism). At the same time, the absolute frequency of this complication in cancer varies widely: it can be either standard for a healthy population (early breast cancer - less than 1%), or extremely high, amounting to 11,7% in cervical cancer
Keywords: Venous thromboembolism; oncogynecological cancer; morbidity